Effect of Urbanization and Growth Rate Population of Expectations Life in Indonesia - Syaifulloh, Muhammad; AN, Gita Ayu; Syamsurijal A Kadir, Syamsurijal A Kadir; Abdul Bashir, Abdul Bashir (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
The driving factor for villagers to urbanize is the lack of jobs in their home areas. Agriculture is the main sector that is relied on by the population, meanwhile, the number of fertility is increasing, which results in unfulfilled needs. Poverty in the village is a driving factor for villagers to migrate. Population growth in an area occurs due to several population factors, including birth (fertility), death (mortality) and also population migration. Population growth is a dynamic balance between the forces that increase and those that reduce the number of people. More and more people are afflicted with a disease means that it will destroy vitality, productivity,